2013
DOI: 10.1002/ece3.758
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic patterns newly established after interspecific hybridization in natural populations of Solanum

Abstract: Interspecific hybridization is known for triggering genetic and epigenetic changes, such as modifications on DNA methylation patterns and impact on phenotypic plasticity and ecological adaptation. Wild potatoes (Solanum, section Petota) are adapted to multiple habitats along the Andes, and natural hybridizations have proven to be a common feature among species of this group. Solanum × rechei, a recently formed hybrid that grows sympatrically with the parental species S. kurtzianum and S. microdontum, represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 39 publications
1
37
0
1
Order By: Relevance
“…Considerable epigenetic differences between natural populations have been reported in other studies, for instance in white poplar (Ma et al 2013), wild potato (Cara et al 2013), and wild barley (Li et al 2008), where epigenetic differentiation of F ST =0.10-0.30 was found. Chwedorzewska and Bednarek (2012) found marked epigenetic differentiation (F ST = 0.5) among Polish and Antarctic annual bluegrass (Poa annua) populations, and Richards et al (2012) reported strong epigenetic differentiation (F ST =0.5-0.8) of Japanese knotweed (Fallopia japonica) populations during invasion into different environments.…”
Section: Kruskalwallismentioning
confidence: 78%
“…Considerable epigenetic differences between natural populations have been reported in other studies, for instance in white poplar (Ma et al 2013), wild potato (Cara et al 2013), and wild barley (Li et al 2008), where epigenetic differentiation of F ST =0.10-0.30 was found. Chwedorzewska and Bednarek (2012) found marked epigenetic differentiation (F ST = 0.5) among Polish and Antarctic annual bluegrass (Poa annua) populations, and Richards et al (2012) reported strong epigenetic differentiation (F ST =0.5-0.8) of Japanese knotweed (Fallopia japonica) populations during invasion into different environments.…”
Section: Kruskalwallismentioning
confidence: 78%
“…These results could be explained by assuming: (1) genetic differences between the diploid and triploid S. microdontum cytotypes, which could have possibly affected nuclear‐cytoplasmic interactions, or (2) aneuploidy in the T×D hybrid progeny. In a previous work (Cara et al ., ), we demonstrated that there were no apparent genetic or epigenetic differences between diploid and triploid S. microdontum cytotypes. Since the same genotypes were used in the present work, the first alternative can be excluded.…”
Section: Discussionmentioning
confidence: 97%
“…& W. (2n = 29 = 24; 2 EBN) and Solanum microdontum B. (2n = 29 = 24; 2 EBN and 2n = 39 = 36), within the limits of their geographic range (Okada & Hawkes, 1978;Cara et al, 2013). Although most S. microdontum populations are diploid, triploid populations have been recorded at the southern end of their range in Argentina (Okada & Hawkes, 1978;Okada, 1981; this work), where they can hybridise with S. kurtzianum.…”
Section: Introductionmentioning
confidence: 99%
“…Loci were discarded if they were monomorphic or if they contained fragments that showed up in any of the negative controls. Following other MS‐AFLP studies (Alonso, Pérez, Bazaga, Medrano, & Herrera, ; Cara, Marfil, & Masuelli, ; also see Zhang & Hare, ), loci were also discarded if they showed too many mismatches among technical duplicates: We allowed a maximum of three mismatches among the set of 24 pairs of technical duplicates. The averaged mismatch error rate (±standard deviation) across all primer combinations used was before purging for T. alatum 8.46 ± 1.70% ( N = 65) and for T. hemicyclum 9.20% ± 1.39% ( N = 72).…”
Section: Methodsmentioning
confidence: 99%